Analysis of Heavy Metal Components in Some Urban Ponds in Rajshahi, Bangladesh (Journal of Life and Earth Science, 2014)
An experiment was conducted to determine the heavy metal pollution status of selected six ponds in Rajshahi City Corporation for a period of 7 months from June, 2008 to December, 2008. Among heavy metals the mean values of Cu, Mn, Zn, Fe and Pb varied from 0.05±0.02 (Pond-5) to 1.79±0.88 mg/l (Pond-4), 21.30±2.64 (Pond-6) to 76.57±30.90 mg/l (Pond-1), 0.08±0.02 (Pond-6) to 1.25±0.79 mg/l (Pond-4), 0.75±0.10 (Pond-3) to 1.87±0.53 mg/l (Pond-5) and 0.14±0.12 (Pond-6) to 4.92±1.66 mg/l (Pond-4) respectively. This study indicated that the Pond-2 covered by garbage, polythene and other wastes, Pond-3 and Pond-4 received industrial wastes were moderately polluted whereas the Pond-1 received City corporation wastes was less polluted. DOI: http://dx.doi.org/10.3329/jles.v7i0.20131 J. Life Earth Sci., Vol. 7: 115-117, 2012